Role and mechanism of short-chain fatty acids in skeletal muscle homeostasis and exercise performance - Liu, X.; Xu, M.; Wang, H.; Zhu, L. (Nutrients, 2025)
Acetate, propionate, and butyrate are major short-chain fatty acids (SCFAs) produced by the gut microbiota as key metabolic byproducts. These SCFAs influence skeletal muscle homeostasis and exercise performance through various mechanisms. This review explores the current knowledge on the mechanisms by which SCFAs influence muscle mass, strength, metabolism, and inflammation. Acetate enhances mitochondrial function and glucose metabolism, while butyrate supports muscle mass preservation by suppressing inflammation and autophagy. Propionate plays complex roles, aiding metabolic regulation, but potentially impairing myogenic differentiation at high concentrations. These SCFAs modulate insulin sensitivity and oxidative stress; their interactions with host energy systems and immunity significantly influence muscle health. Although their therapeutic potential is evident, further studies, especially human clinical trials, are necessary to validate their effective applications. This review synthesizes emerging evidence and outlines specific future research priorities.